Penggunaan Metode Bercerita untuk Mengatasi Kesulitan Komunikasi Siswa Tunarungu di SLB GMIM Nazareth Tuminting - Ria Mananeke (Peneliti.net, 2021)
This study aims to describe the application of storytelling communication for hearing impairment children in special schools GMIM Nazareth Tuminting. This study uses a classroom action approach (PTK), with two cycles. The subjects of the study were the second grade students of SLB GMIM Nazareth Tuminting, which means 4 children. The results showed Cycle I: (a) At the first meeting the children seemed to be a bit stiff with a busy classroom situation, because everyone wanted to talk. The response shown by the child will come out after the teacher pays special attention by asking the child to give an open opinion about the story the teacher tells. (b) The teacher's level of class mastery is still lacking, (c) The classroom atmosphere when telling stories is still too busy, so it is necessary to regulate who can talk when the teacher asks questions, (d) The pictures used by the teacher in supporting the story must be more interesting. Whereas Cycle II: (a) At this second meeting the child who is more courageous to speak, likes to express what he thinks, and is not stiff to ask the teacher and suggestions, (b) The classroom atmosphere is organized, the teacher is able to carry out learning according to the flow and sequence appropriate So that children can regularly follow the stories told by the teacher, (c) The pictures used by the teacher are interesting and in accordance with the contents of the story. In addition, storytelling activities besides helping children's language development, can also build a close relationship between teacher and child. Through the storytelling method, the teacher can be received intimately and affectionately with students. After implementing two learning cycles of communication, it can be said that the storytelling method can overcome the difficulties of deaf students.